INVESTIGATION OF COMPONENTS OF THE BINARY SYSTEM 38 PER - Lyubimkov, L. S.; Rachkovskaya, T. M.; Rostopchin, S. I.; Tarasov, A. E. (Одеські астрономічні публікації, 2017)
Radial velocities VT of components of the binary system 38 Per are measured using high resolution and high signal / noise ratio spectra. The orbital elements were updated on the basis of these data and early published measurements of Vr. The following values of effective temperature and surface gravity for the secondary component (star B) are found from its spectral type B2V and the statistical relation of de Jager and Nieuwenhuijzen (1987): Teff =21000 ±1500K lgg =4.0 ±0.2. Using these values we found the fundamental parameters for the primary component (star A): Teff = 22700 ±1500 K and lgg =3.4 ±0.2 The rotational velocities of the components are measured from Hel lines: vsin i =80 ±7 kms-1 for A and vsin i =95 ±10 kms-1 for B. The atmospheric helium abundance is determined; it is relatively high for A (He/H = 0.19 ±0.06) and nearly normal for B (He/H = 0.11 ±0.03). From evolutionary tracks the relative ages of the components t/tMS (A) = 0.96 ±0.05 and t/tMS (B) =0.54 ±0.03 are determined, i.e. the primary is near the end of the main sequence (MS) phase and the secondary is near the middle of this phase. This investigation together with our previously results for α Vir (Lyubimkov et al., 1995), V380 Cyg (Lyubimkov et al., 1996) and 45 6 Per (Tarasov et al., 1995) confirms the correlation between the helium abundance and the stellar age. An explanation may be connected with mixing already on the MS phase. Full version of this paper will be submitted in Astronomicheskij Zhurnal.